Estudo e comparação de técnicas de controle não lineares aplicadas a conversores estáticos de potência - Arthur Hermano Rezende Rosa (2015)
The control of power converters is a recurring problem in the literature and fits nowadays context that consolidates energy efficiency as a keypoint in technology and sustainable development. Thus, this thesis aims to study and compare nonlinear control techniques applied to static power converters, namely: Buck, Boost, Buck-boost, Flyback, Sepic andCuk. Although they are basic building blocks in electronics, these converters have been attracting growing interest in the power electronics and control areas. This is due to the diversity of applications including from household appliances to sophisticated electrical systems. Greater emphasis is given to the boost converter because it is the only converteranalyzed with power factor correction (PFC), since it is the most suitable for this specific application. The other systems are analyzed as control voltage regulators (DC-DC) in which the input voltage comes up to a constant value. Due to a vast new field for nonlinear controls of converters, because they offer a more natural response and, especially, make electronic systems more efficient, nonlinear control algorithms areobtained and implemented: state feedback linearization (SFL), passivity based control (PBC) and interconnection and damping assignment passivity-based control (IDA-PBC). Taking into account that many control laws require validation, this work employs high level programming with MATLAB/ DSP integration and Hardware In the Loop (HIL) simulation. This methodology facilitates the testing and collection of results and reduces the development cycle of the project.